Implementation of CMM Method to Measure Maturity Level of SPBE in Palembang City Government - Nyimas Hamidah Purnama Agustriani; Marsudi Wahyu Kisworo; Edi Surya Negara; Usman Ependi (Politeknik Ganesha Medan, 2026)
The Palembang City Government faces challenges in synchronizing internal policies with the operational implementation of the Electronic-Based Government System (SPBE). This research aims to measure the maturity level of the Internal Policy Domain and the SPBE Governance Domain in the Palembang City Government using the Capability Maturity Model (CMM) method. Additionally, the study aims to identify gaps through gap analysis and formulate strategic recommendations to achieve the